THE EFFECTIVENESS OF SUGGESTOPEDIA IN TEACHING READING COMPREHENSION OF NARRATIVE TEXT - Faidatun, Nella (2013)
The study focused on the effectiveness of Suggestopedia in teaching reading comprehension of narrative text and students' responses toward the implementation of the method. A quasi experimental design as a part of quantitative research was employed in this study. The data were obtained through the pre-test, post-test and questionnaire. The sample was 80 students of eight graders. One class as an experimental group in which Suggestopedia was applied and one class as a control group which used convetional method. In the findings, it was shown that the use of suggestopedia was effective in teaching reading comprehension of narrative text as indicated by statistical computation in the post-test score of experimental group (M=74.90) and the post-test score of control group (M=65.90). Based on the independent t-test result, the tobt (5.125) is greater than tcrit (1.92) at the level of significance 0.05 which means that the null hypothesis was rejected. In other words, there was a difference between the experimental group and the control group. Furthermore, it was also supported by the student's responses from the questionnaire. The data showed that most of students in experimental group were enthusiastic to the implementation of suggestopedia. Keywords: suggestopedia, reading comprehension, narrative text. Penelitian ini mengkaji tentang keefektifan metode Suggestopedia pada pengajaran pemahaman membaca teks naratif dan tanggapan siswa terhadap penggunaan metode tersebut. Penelitian Semu sebagai bagian dari penelitian kuantitatif digunakan dalam penelitian ini. Data diperoleh dari pre-test, post-test dan kuesioner. Objek penelitian merupakan 80 siswa kelas 8 dimana 1 kelas menjadi kelas eksperimen yang menggunakan metode Suggetopedia dan 1 kelas lain menjadi kelas kontrol yang menggunakan metode konvensional . Berdasarkan hasil penelitian, penggunaan metode Suggestopedia efektif dalam pengajaran pemahaman membaca teks naratif. Hal ini dibuktikan dari hasil perhitungan data statistik dari perolehan nilai post-test di kedua kelas. Nilai rata-rata post-test di kelas eksperimen adalah 74.90, sedangkan perolehan rata-rata nilai post-test di kelas kontrol 65.90. Hasil perolehan uji-t membuktikan bahwa tobt lebih besar dari tcrit (5.125 > 1.92) pada tingkat signifikansi 5%, sehingga ada perbedaan antara kelas eksperimen dan kelas kontrol setelah diberikan perlakuan. Perolehan data dari kuesioner juga menyatakan bahwa siswa memberikan tanggapan positif terhadap penggunaan metode tersebut. Kata Kunci: suggestopedia, pemahaman membaca, teks naratif